Presenteeism and Its Associated Factors Among Teachers - Serya, Hend; El-Gilany, Abdel-Hady (La Medicina del Lavoro, 2025)
Background: Teaching is a mentally and physically demanding profession, often performed under challenging and stressful conditions. In Egypt, the lack of school resources, low teacher salaries, poor organizational climate, and high work pressures represent just a few challenges faced by the educational system. These difficulties can adversely affect teachers' health, leading to negative outcomes such as presenteeism. Despite this, no studies have assessed presenteeism among Egyptian teachers. Therefore, this study aimed to estimate the prevalence of presenteeism and identify associated factors among public school teachers. Methods: A cross-sectional study was conducted involving 373 teachers using an interview-administered questionnaire to gather information on their sociodemographic, occupational, and medical characteristics, along with their Stanford Presenteeism Scale scores and responses to the Job Content Questionnaire.Results: The prevalence of presenteeism among the teachers studied over the last 12 months was 70.8%. Of these, 74.6% had lower presenteeism scores, reflecting diminished performance in work activities. Key independent predictors of presenteeism included being a female teacher, having additional jobs, experiencing musculoskeletal and/or respiratory health issues, facing high job demands, and possessing low job control. The Adjusted Odds Ratios (AOR) for these factors were 4.1, 5.1, 3.1, 11.7, and 11.7, respectively. Conclusion: Presenteeism is highly prevalent among public school teachers in Egypt. Therefore, teachers with significant predictors of presenteeism should be given increased attention.